2014
DOI: 10.1002/pbc.25354
|View full text |Cite
|
Sign up to set email alerts
|

Extraneural metastases of medulloblastoma: Desmoplastic variants may have prolonged survival

Abstract: Extraneural metastases from medulloblastoma may rarely develop after initial diagnosis to involve bone and bone marrow. We found that desmoplastic variant extraneural tumors had longer survival than nondesmoplastic variants, suggesting that histopathological and more recent molecular subtyping have important roles in determining the prognosis of medulloblastoma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…15 High grade malignancies, such as retinoblastoma and medulloblastoma seem to retain their high grade histologic appearance within metastatic foci. 13,14 While metachronous and distant extranueral metastases cannot be completely ruled out in the case presented, the histomorphology of the cutaneous lesions does not resemble that of the AT/RT. In fact the resemblance is much closer to that of ES.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…15 High grade malignancies, such as retinoblastoma and medulloblastoma seem to retain their high grade histologic appearance within metastatic foci. 13,14 While metachronous and distant extranueral metastases cannot be completely ruled out in the case presented, the histomorphology of the cutaneous lesions does not resemble that of the AT/RT. In fact the resemblance is much closer to that of ES.…”
Section: Discussionmentioning
confidence: 74%
“…12 Despite their rarity, metastases from high grade CNS malignancies have been documented multiple years after their original diagnosis in subjects with longer term survival. 13,14 Sites of extraneural metastases from CNS lesions include viscera, bone, soft tissue, and skin. 15 High grade malignancies, such as retinoblastoma and medulloblastoma seem to retain their high grade histologic appearance within metastatic foci.…”
Section: Discussionmentioning
confidence: 99%
“…Although molecular subtype data was not available in the largest reported series of extraneural metastatic MB [ 5 ], the correlation between desmoplastic histology and SHH activation [ 12 ] suggests that the majority of long-term survivors belong to the SHH-MB subgroup [ 5 ]. Similar to our case, most of desmoplastic MB patients only received CSI as the initial treatment, raising the question of the validity of systematic chemotherapy to eradicate subclinical metastatic extraneural disease in this MB subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with recurrent SHH-MB, survival is dismal [ 2 ]. Although disease recurrence is usually confined within the CNS, extraneural metastases may rarely develop [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…MB commonly spreads through the cerebrospinal fluid (CSF) and disseminates to the surfaces of the brain and spinal cord. The overall 5-year survival rate of patients with MB is approximately 70 % [1, 2]. Many studies have demonstrated that tumor dissemination (seeding) into the cerebrospinal fluid may have the strongest impact on patient prognosis [3, 4].…”
Section: Introductionmentioning
confidence: 99%